Optimalisasi Promosi Wisata Edukasi Taman Kreatif Melalui Pelatihan Media Sosial di Kampung Pipitan - Dera Alfiani; Hanifah Fajriani; Rabeka Herdiani; Sunjaya Sunjaya; Ail Muldi; Neka Fitriyah (Peneliti.net, 2022)
This journal contains the process of implementing the Creative Park educational tourism development training program through social media as an optimization of promotion in Pipitan Village, Walantaka District, Serang City. The purpose of this study was to analyze the implementation of the training program for the development of social media for educational tourism at Taman Kreatif by using a brief socialization method which included several stages of implementing activities, namely preparation, implementation, and evaluation. The preparation stage consists of two main things, namely field observations and literature review. Sources of data in the study obtained through interviews and documentation. The results of this study indicate that the lack of promotion through social media Instagram is carried out optimally. This is shown by the many accounts belonging to the Creative Park educational tour, but not many of them are active and the social media used is not up to date. In the implementation of this program, there is also a training process on the use of social media for the surrounding community in order to be able to promote the Creative Park educational tourism to the fullest